PSYCHOLOGICAL STUDY OF THE CREATIVITY OF A MODERN MANAGER - Poghosyan , S.H. (Modern Psychology, 2021)
Nowadays the training of the managers requires improvement, which implies training a creative manager, who can work in uncertain and emergency situations. People who express their creativity have special personality traits. However, the correlation of the creativity and personality traits in management has not been sufficiently studied. It is also necessary to study the creativity methods based on the correlation between creativity and personality traits. If we consider creativity as the core system-creating quality for all traits, we can assume which traits of a person will be displayed in case of the expression of creativity. The purpose of this article is to study the creativity of a specialist as a system creating quality. Combined with the personality traits and the application of creativity methods it ensures the proposal of unique and new ideas. For this purpose we did research. We used the tests by F. Williams for creativity assessment and for discovering the individual qualities of a creative person, Cattell's 16 Personality Factors Test, Ryff`s Psychological Wellbeing Scale. Thus, for the creative solution of the problem, personal traits are needed, which will help to express the standards of creativity. However, appropriate methods, motivation and psychological security are needed for the effectiveness of the creative process in professional activities.
Keywords: creativity; personality; manager; psychological well-being; research; unique